Community-based interventions for mitigating cognitive-linguistic decline in older adults - Tian, Xiaoming; Ding, Wenshu (Frontiers in Psychiatry, 2024)
Introduction: This study focuses on exploring the effectiveness of interventions in two community-based language rehabilitation care centers located in an economically underdeveloped region of northwest China. Method: The research focuses on 35 older adults with cognitive-linguistic decline enrolled in both centers. The interventions provided to the participants include auditory training, sign language use enhancement, second language interest classes, and the promotion of elderly-mode applications on smartphones. Results: The interventions were particularly effective in enhancing auditory processing and language comprehension skills. Additionally, the promotion of elderly-mode applications on smartphones proved to be a valuable tool in improving participants’ language cognition. Conclusion: The study underscores the importance of tailored community-based interventions in improving language skills and cognition and provides a basis for further research in this area.